A Poisonous Legacy: The Hidden Story of an Early Experimental Practice - Tarrant, Neil (Incontri. Rivista europea di studi italiani, 2024)
Review of Alisha Rankin, The Poison Trials: Wonder Drugs, Experiment and the Battle for Authority in Renaissance Science (Chicago and London: University of Chicago Press, 2021), pp.329.